Alternative Religiosity in Communist Yugoslavia: Migration as a Survival Strategy of the Nazarene Community - Milovanović, Aleksandra Djurić (Open theology, 2017)
The Nazarenes were founded by a former Reformed minister Samuel Fröhlich about 1830 in Switzerland, but they soon expanded to Central and Eastern Europe. Because of their pacifist beliefs and refusal to swear and to take an oath a large number of the Nazarenes were condemned to severe prison sentences. This religious community was persecuted primarily during the communist era in Southeastern European countries (Hungary, Romania, Yugoslavia) since they were considered disloyal citizens and a threat to the government. From 1945 until 1960 the Nazarene illegal border crossing from Yugoslavia to Italy or Austria was highly present. Rejecting one of the essential components of Yugoslav communism, so-called “nationwide defence and social self-protection”, the Nazarenes were perceived as anti-communists and their existence was seen as illegitimate. The repression of this religious minority in communist Yugoslavia is the subject of this paper. The material collected for the purposes of this paper came to be the result of empirical research, conducted in Serbia (2009-2013) and the United States (2015), on the Nazarene community and their emigration to North America. Based on qualitative interviews and archival research, this paper aims to analyse community members’ narratives of their lives during communism and emigration of this religious minority across the Atlantic.